743 Lysosomal Storage Disorders in Non-Immunological Hydrops Fetalis - More Common than Assumed?. (October 2012) - Whybra, C; Mengel, E; Bahlmann, F; Kampmann, C; Beck, M; Mildenberger, E
Abstract : Background: Although non immunological hydrops fetalis (NIHF) is a very rare disorder, the disturbance accounts for a disproportionate share (3%) of overall mortality in the perinatal period. Lysosomal storage disorders (LSD) are only exceptionally considered to be the cause of NIHF. The reported incidence is about 1%. On the other hand, in about 18% of all cases, NIHF is classified as idiopathic. Patients and methods: We report four cases of transient NIHF due to LSD and reviewed the literature for LSD associated with NIHF. Results: At present, 12 different LSD are described to be associated with NIHF. The majority of reported patients already had a family history of NIHF, which had not been investigated. A diagnostic approach to the fetus with NIHF due to suspected LSD is suggested. Conclusions: Extensive and thorough investigation of the etiology of NIHF is obligatory. In particular, LSD should be considered in idiopathic NIHF. Enzymatic studies in chorionic villous samples or amniotic cultured cells, once the most common conditions associated with NIHF have been ruled out, should be performed. We assume that the incidence of LSD in NIHF is significantly higher than the estimated 1% reported in previous studies. This is important for genetic counseling, as there is at first, a high risk of recurrence and, secondly, the availability of enzyme replacement therapy for an increasing number of LSD.